Feasibility analysis of hybrid energy generation systems for desert highway service areas: a case study in northern Xinjiang, China - Wang, Guangtao; Zhang, Yufei; Tang, Wenbin; Liao, Zhen; Wang, Teng; Zhang, Shuo; Zhao, Xin (Frontiers in Energy Research, 2024)
Highways consume a significant amount of electrical energy annually, especially in remote desert regions where the cost of electricity is high. This research explores the utilization of natural resources along desert highways to establish hybrid energy generation systems for service areas. Three service areas along the desert highway in northern Xinjiang, China, serve as case studies. To assess the feasibility of hybrid energy generation systems in these service areas, meteorological data for the three locations were obtained from the NASA platform. The HOMER Pro software was employed for technical, economic, and environmental analyses of the systems. The results indicate the feasibility of Photovoltaic (PV)/Wind/Battery hybrid energy systems in the Huanghuagou, Kelameili, and Wujiaqu service areas. The application of these hybrid energy generation systems across the three service areas could provide 3,349,557 kWh of electrical energy annually for the desert highway. Sensitivity analysis reveals that the Net Present Cost (NPC) and Cost of Energy (COE) values decrease with increasing radiation levels, while NPC shows an increasing trend with growing load demand, and COE exhibits a decreasing trend. Among the three regions, Wujiaqu demonstrates the highest economic viability, with a COE of 0.34/kWh and an NPC of 3,141,641/kWh. Furthermore, Wujiaqu exhibits the lowest environmental impact, with CO2 emissions of 198,387 kg/yr, SO2 emissions of 493 kg/yr, and NOx emissions of 1,711 kg/yr.